2014
DOI: 10.1002/anie.201402433
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of α‐Azidoesters and Geminal Triazides

Abstract: Three simple methods for the synthesis of geminal triazides are described: Starting from 1) 3-oxocarboxylic acids, 2) iodomethyl ketones, or 3) terminal olefins, a range of triazidomethyl ketones can be constructed under mild oxidative reaction conditions by the use of IBX-SO3 K, a sulfonylated derivative of 2-iodoxybenzoic acid (IBX), and NaN3 as an azide source. This is the first report of representatives of this novel class of triazide compounds: Despite their high nitrogen content, the geminal triazides ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 98 publications
0
63
0
4
Order By: Relevance
“…These properties could fit the requirements for suitable additives in propellant formulations. (4) > 360 N > 40 J insensitive b-1,3-DAPM (5) 160 N 35 J sensitive b-2,3-DAPM (6) 160 N 35 J sensitive DA-bAEM (7) 36 N 1 J very sensitive DA-b-2,3-DAPM (8) 36 N < 1 J very sensitive DA-b-1,3-DAPM (9) 36 N < 1 J very sensitive…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These properties could fit the requirements for suitable additives in propellant formulations. (4) > 360 N > 40 J insensitive b-1,3-DAPM (5) 160 N 35 J sensitive b-2,3-DAPM (6) 160 N 35 J sensitive DA-bAEM (7) 36 N 1 J very sensitive DA-b-2,3-DAPM (8) 36 N < 1 J very sensitive DA-b-1,3-DAPM (9) 36 N < 1 J very sensitive…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical and energetic properties of the three new geminal diazidated azido malonic acid esters are shown in Table 1. They were compared to the synthesized precursor azido esters (4)(5)(6). The energetic parameters like heat of combustion, detonation pressure, detonation velocity and volume of gaseous products were calculated using version 6.03 of Explo5 [13].…”
Section: Physicochemical and Energetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…‡ 7 A variant of this procedure also led to the synthesis of geminal triazides, highly energetic compounds that must be handled with caution. 8 In the course of those projects, we realized that the di-and triazides can be converted into their corresponding geminal bis-and tristriazoles using cycloaddition reactions with alkynes. 9 Besides our own reports, the two compound classes turned out to be somewhat neglected, and most previous reports on geminal bistriazoles focused on geminal bis(benzotriazol-1-yl)methyl derivatives, as shown, for example, in the detailed studies by 11 Even more surprising, our review of the literature revealed only one example for a geminal tristriazole, i.e.…”
mentioning
confidence: 99%